1996
DOI: 10.1051/aas:1996276
|View full text |Cite
|
Sign up to set email alerts
|

A 15 years monitoring program at 408 MHz

Abstract: Abstract. -This is the second paper based on the 408 MHz monitoring program with the East-West arm of the Bologna interferometer. The monitoring concerned 125 radio sources measured approximately once a month for 15 years. We present the summary of the variability analysis concerning all the sample and the monitoring data, not yet published, of the variable sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 4 publications
4
43
0
Order By: Relevance
“…In the minority of the low-frequency variable sources (LFV), the variability is correlated with that at high frequencies, with events started at high frequencies and propagated to low frequencies with decreasing amplitude. This is a signature of intrinsic variability caused by expansion of the emitting region, which has been confirmed from a comparison between flux density variability at 408 MHz and structural changes observed with VLBI observations at 1.67 GHz in several LFV sources (Bondi et al 1996). The majority of sources selected on the basis of LFV, however, showed no correlation between variability at low and high frequencies, which has been interpreted in terms of extrinsic variability due to refractive interstellar scintillation (e.g., Bondi et al 1994, and references therein).…”
Section: Correlations Between Radio Properties Of the Jetsupporting
confidence: 64%
“…In the minority of the low-frequency variable sources (LFV), the variability is correlated with that at high frequencies, with events started at high frequencies and propagated to low frequencies with decreasing amplitude. This is a signature of intrinsic variability caused by expansion of the emitting region, which has been confirmed from a comparison between flux density variability at 408 MHz and structural changes observed with VLBI observations at 1.67 GHz in several LFV sources (Bondi et al 1996). The majority of sources selected on the basis of LFV, however, showed no correlation between variability at low and high frequencies, which has been interpreted in terms of extrinsic variability due to refractive interstellar scintillation (e.g., Bondi et al 1994, and references therein).…”
Section: Correlations Between Radio Properties Of the Jetsupporting
confidence: 64%
“…VLBI observations at 1667 MHz of PKS 1127-145 (Bondi et al 1996) have shown that it has a core-jet structure, with a total size less than ∼ 20 milli-arcseconds. This small size implies that the covering factor of the absorbing system is likely to be close to unity.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…At higher frequencies, the Metsähovi group (Teräsranta et al 1998) have reported observations at 22, 37 and 87 GHz of 157 extragalactic radio sources, many of which have been monitored for over 20 years. The Bologna group (Bondi et al 1996) have observed at 408 MHz 125 radio sources for 15 years. A multifrequency monitoring of a large sample of compact radio sources has been carried out by Kovalev et al (2002) with the RATAN-600 telescope.…”
Section: Introductionmentioning
confidence: 99%